Mekanisme Pelaksanaan Restitusi Terhadap Korban Kekerasan Seksual (Studi Komparatif Hukum di Indonesia dan Thailand) - Azzahra, Jazmine; Lubis, Muhammad Teguh Syuhada (Universitas Muhammadiyah Ponorogo, 2025)
Sexual harassment constitutes a form of sexual violence that significantly impacts victims, including psychological, physical, and economic aspects. The mechanism of restitution as a means of restoring the rights of victims has been established through various legal provisions in Indonesia, namely Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS). Meanwhile, Thailand also regulates restitution mechanisms as a form of victim recovery as outlined in the Child Protection Act of 2546 (2003). However, the implementation of restitution often faces various obstacles, including technical and legal issues. This study aims to examine the mechanisms for implementing restitution for victims of sexual harassment in Indonesia and Thailand, identify emerging obstacles, and present structured proposals for its successful application. Based on normative legal reviews, the study reveals that although regulations are in place, their implementation remains suboptimal due to the lack of inter-agency coordination, limited public legal awareness, and the complexity of calculating compensation for victims. The findings on restitution provisions for sexual harassment victims in Indonesia are regulated through several legal instruments, including Law No. 31 of 2014 in conjunction with Law No. 13 of 2006 on the Witness and Victim Protection Agency, Law No. 12 of 2022 on Sexual Violence Crimes, and Government Regulation No. 35 of 2020 in conjunction with Government Regulation No. 7 of 2018 on Compensation, Restitution, and Assistance for Witnesses and Victims.